2016
DOI: 10.1007/s11655-016-2597-8
|View full text |Cite
|
Sign up to set email alerts
|

Tounong Powder (透脓散) extracts induce G1 cell cycle arrest and apoptosis in LoVo cells

Abstract: TNSEs reduced LoVo cell proliferation, and caused apoptosis and cell-cycle arrest in LoVo cells. This effect might be associated with regulation of the PI3K/AKT signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Subsequently, precise ultrasound-guided debridement surgery was performed. After 2 months of conventional dressing change and treatment with Traditional Chinese Medicine ( 19 ), the lesion had healed and the mass had subsided.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, precise ultrasound-guided debridement surgery was performed. After 2 months of conventional dressing change and treatment with Traditional Chinese Medicine ( 19 ), the lesion had healed and the mass had subsided.…”
Section: Resultsmentioning
confidence: 99%
“…During the treatment, obstruction of the negative pressure drainage tube was avoided, the amount and characteristics of the drainage fluid were observed and the negative pressure drainage material was replaced once a week. Traditional Chinese Medicine, such as Tounong Powder ( 19 ), was administered according to the symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…), Zao Jiao Ci ( Gleditsia sinensis Lam. ), Chuan Shan Jia ( Manis pentadactyia Linnaeus) LoVo Proliferation ↓, Apoptosis ↑, Block cell cycle ↑: cleaved caspase-3,cleaved caspase-9 ↓: PI3K,p-AKT, p-mTOR, p-p70s6k1 PI3K/Akt [ 56 ] Jiedu Sangen decoction (JSD) Pu Gong Ying Gen ( Taraxacum mongolicum Hand. –Mazz.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 55 ] found that Gegen Qinlian Decoction (GQD) could inhibit CT-26 CRC growth accompanied by upregulation of p-PI3K, p-Akt, phosphorylated forkhead box transcription factor O1 (p-FOXO1), and ankyrin repeat and BTB/POZ domain containing protein 1 (ABTB1). Fang et al [ 56 ] found that Tounong powder extracts (TNSEs) induced LoVo cell growth inhibition in a dose- and time-dependent manner; significantly downregulated the expression of PI3K, p-AKT, phosphorylated mechanistic target of rapamycin (p-mTOR), and p-p70s6k1; and upregulated the expression of cleaved caspase-9 and -3. These findings suggested that TNSEs may inhibit LoVo cells through the PI3K/Akt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%